Effects of castration age and a growth implant during suckling on weaning and preconditioned weights - T.T. Marston; Donald A. Llewellyn; J.W. Homm; Larry C. Hollis (Kansas Agricultural Experiment Station Research Reports, 2003)
Crossbred Angus calves (n=141) were used to determine the effect of castration age and implant on weaning and preconditioned weights. Calf treatments consisted of: early castration at 90 days of age with no growth implant, early castration with a growth implant (Synovex C) at 90 days of age, or late castration at weaning (226 days of age). All calves completed a preconditioning program that consisted of timely vaccinations (21 days prior and at weaning) and a 28-day, post-weaning feeding period. Steers that were early castrated/implanted had weaning weights similar to those of bull calves, and both groups weighed 15 lb more than their early castrated/no implant contemporaries. However, 28 days after weaning the early castrated/ implanted steers weighed 20 lb more than either the early castrate/no implant or late castrated steers. Our data indicate that early castration in combination with a suckling phase implant produces the greatest amount of saleable weight along with the most flexibility in marketing options.
Keywords: Cattlemen' s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Castration; Preconditioned weights; Weaning weights